2018
DOI: 10.1021/acsnano.7b08264
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic Microparticles Increase the Potency of Rifampicin against Intracellular Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis ( M.tb) has the extraordinary ability to adapt to the administration of antibiotics through the development of resistance mechanisms. By rapidly exporting drugs from within the cytosol, these pathogenic bacteria diminish antibiotic potency and drive the presentation of drug-tolerant tuberculosis (TB). The membrane integrity of M.tb is pivotal in retaining these drug-resistant traits. Silver (Ag) and zinc oxide (ZnO) nanoparticles (NPs) are established antimicrobial agents that effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Threats posed by bacterial infections are of major public concern, leading to a boost in efforts to develop new antimicrobial agents. 1 The use of silver nanoparticles (AgNP) has been widely explored, [2][3][4] showing antimicrobial activity in the dark and under illumination. 5,6 Whereas some studies suggest silver nanoparticles are a simple source of silver ions, 7 a few years back our group demonstrated that the mechanism is more complex 8 and may involve direct action by the nanoparticles themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Threats posed by bacterial infections are of major public concern, leading to a boost in efforts to develop new antimicrobial agents. 1 The use of silver nanoparticles (AgNP) has been widely explored, [2][3][4] showing antimicrobial activity in the dark and under illumination. 5,6 Whereas some studies suggest silver nanoparticles are a simple source of silver ions, 7 a few years back our group demonstrated that the mechanism is more complex 8 and may involve direct action by the nanoparticles themselves.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that a variety of transition metals can be advantageous in the treatment of pulmonary bacterial ailments. Ag, Cu, Fe, Pd, and Zn have been suggested for tuberculosis (TB) (Chao A. et al, 2019;Ellis T. et al, 2018;Palazzo F. et al, 2013;Pieters J., 2008;Poole K., 2017), Ag and Pt for lung cancer (with some evidence of dose-dependent toxicity) (Foldbjerg R. et al, 2011;Ndagi U. et al, 2017), and Ag, Cu, and Zn for viruses, including coronavirus (Bright K.R. et al, 2008;Raha S. et al, 2020;Ranford J.D.…”
Section: Aerosols For Pulmonary Therapymentioning
confidence: 99%
“…A similar effect of multimetallic nanoparticles (MMN) including AgNP for intramacrophagic mycobacteria was reported by Ellis etal. 218 Although internalized within the phagolysosomal apparatus, the AgNP have a limited antitubercular effect for the intracellular bacteria, but increase the antitubercular effect of rifampicin. The co-administration of rifampicin led to a reduction of 68% of M. tuberculosis colony-forming units.…”
Section: In Vitro Studiesmentioning
confidence: 99%